2006
DOI: 10.1094/cc-83-0439
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rice Proteins on Eating Quality of Cooked Rice and on Aroma and Flavor of Sake

Abstract: Cereal Chem. 83(4):439-446An improved method for the extraction of storage proteins from rice endosperm under conditions safe for producing food was developed. The contribution of the protein extracts to the eating quality of cooked rice and to the aroma and flavor of sake was examined. Sensory analysis was performed to evaluate the eating quality of cooked rice enriched with the protein extracts. Prolamin-enrichment increased the hardness of cooked rice, and glutelin-enrichment degraded the appearance of cook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…2G-2I); therefore, LGC-Jun would also be useful in a low protein diet. The PB amount and the related polypeptide content have been reported to be closely related not only to protein digestibility, but also to cooking and sake brewing properties (Baxter et al 2004, Furukawa et al 2006. Thus, it is important to clarify the PB structure in order to evaluate the processing aptitude of mutant rice with altered storage protein composition.…”
Section: Ultrastructure Of Protein Bodies During Seed Developmentmentioning
confidence: 99%
“…2G-2I); therefore, LGC-Jun would also be useful in a low protein diet. The PB amount and the related polypeptide content have been reported to be closely related not only to protein digestibility, but also to cooking and sake brewing properties (Baxter et al 2004, Furukawa et al 2006. Thus, it is important to clarify the PB structure in order to evaluate the processing aptitude of mutant rice with altered storage protein composition.…”
Section: Ultrastructure Of Protein Bodies During Seed Developmentmentioning
confidence: 99%
“…Protein content and protein composition are important factors infl uencing the quality of cooked rice (Masushige et al 1994;Furukawa et al 2006) as well as the aroma and fl avor of sake (Furukawa et al 2004(Furukawa et al , 2006. In addition, rice fl our has recently attracted keen interest as food material, and various new foods using rice fl our have been developed, including rice flour bread, rice flour noodles and various rice confectioneries.…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that DOWC might have affected the metabolic properties of microbial winemaking [13,15,30], and different rice ingredients had their own unique flavors [12]. If DOWC affects the decomposition of rice protein by microorganisms, it means that different amino acids and peptide metabolites will be further produced during the wine brewing process [9,14], which will affect the final flavor characteristics of the sample. As a result, DOWC has created a combination of different volatile/aromatic compounds in both Taichung No.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…The released amino acids and peptides create the aroma and taste of brewed sake and are used as major nutrient sources for yeast growth in the sake brewing process. Therefore, it is important to control the digestion and levels of rice protein during the sake brewing process [9]. Analyzing the content and threshold of candidate compounds helps to identify the characteristics of the brewing conditions, such as the type of rice koji used, the type of rice, and the type of shochu.…”
Section: Introductionmentioning
confidence: 99%